The Role of Computer Education in the Behavioral Intentions to Use Information Technology in Hospitals in Kumasi, Ghana - Osei, Ernest; OPPONG, PETER KWASI (Journal of Economics and Behavioral Studies, 2020)
Computer education is increasing steadily because it is well-recognized as a major indicator of the successful acceptance of information technology applications in an organization. Despite the advantages associated with computer education, there is a relative scarcity of empirical studies on the potential role of computer education in the behavioural intentions of staff to use information technology applications, particularly in healthcare settings. Thus, this research is aimed to investigate the role of computer education to the behavioural intentions of staff to use information technology applications in the hospitals in Kumasi. Guided by Davis` technology acceptance model, five hypotheses were stated and examined through structural equation modeling. Utilizing stratified sampling, data were gathered via a survey questionnaire from a sample of 154 staff in the hospitals in Kumasi. The research revealed that computer education contributes positively to the behavioural intentions to use via the impact of perceptions of ease of use of technology applications in the hospitals in Kumasi. The research, therefore, recommends that the management should consider computer education in the adoption of technology systems to enhance the staff perceptions of ease of use and hence, their intentions to use to improve health care in the Metropolis.